2010
DOI: 10.1039/c0an00322k
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid integration of injector and detector functions for microchip gas chromatography

Abstract: Hybrid microchips containing high aspect ratio gas chromatograph (GC) columns with an integrated on-chip split injection and a flame ionization detector were developed. Two different column configurations, spiral and serpentine, both 1 m long by 50 μm wide and 500 μm tall, were fabricated out of electrodeposited nickel. The hybrid chip allowed injection plugs on the order of 1-2 ms, which lowered the height equivalent to theoretical plates (HETP) and allowed a comparison of system level band broadening between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In order for micro-PCs to function in a chemical analysis system, they need to be connected to other components such as separation columns and sensors. Unless they are monolithically integrated [18], each of these components is modularly integrated and typically connected via polyimide-coated glass capillary tubing [46,47]. The majority of micro-PCs are silicon based, which is brittle and difficult to machine for fluidic connections.…”
Section: Resultsmentioning
confidence: 99%
“…In order for micro-PCs to function in a chemical analysis system, they need to be connected to other components such as separation columns and sensors. Unless they are monolithically integrated [18], each of these components is modularly integrated and typically connected via polyimide-coated glass capillary tubing [46,47]. The majority of micro-PCs are silicon based, which is brittle and difficult to machine for fluidic connections.…”
Section: Resultsmentioning
confidence: 99%
“…The authors attribute the enhanced separation performance of the serpentine design to favorable hydrodynamic flow as well as thinner and more homogeneous stationary-phase coating in serpentine configuration. Bhushan et al, 77 using methane as an unretained marker, showed that circular-spiral and serpentine column layouts exhibit similar flow and band broadening. The band broadening effect for retained compounds was not evaluated.…”
Section: Analytical Chemistrymentioning
confidence: 99%